HUBUNGAN ANTARA STATUS GIZI DENGAN USIA MENARCHE PADA REMAJA SISWI KELAS 4, 5 DAN 6 DI SDN DAWUHAN LOR 01 KECAMATAN SUKODONO LUMAJANG - Fety Dwi Anggraini; Nova Hikmawati; Sri Wahyuningsih (Health and Technology Journal (HTechJ), 2023)
Menstruation for the first time in young women is called menarche which is experienced by girls aged 11 to 14 years. Recently, few researche show there is an earlier age of menarche because of higher nutritional status. The purpose of this study was to determine the relationship between nutritional status and the age of menarche in female students in grades 4, 5, and 6 at Dawuhan Lor 01 Public Elementary School, Sukodono District, Lumajang Regency. The analytic correlation research design with a cross- sectional time approach was used on 39 respondents at Dawuhan Lor 01 Public Elementary School, Sukodono District, Lumajang Regency. Measuring tools in this study were respondent characteristic questionnaires, nutritional status observation sheets, and menarche age. Spearman's rho test was used to answer the purpose of this study. The results showed that the majority of female students had good nutritional status as many as 29 female students (74.4%). The majority of female students have normal menarche age (11-13 years) as many as 24 respondents (61.5%). There is a significant relationship between nutritional status and the age of menarche in grades 4, 5, and 6 at SDN Dawuhan lor 01, Sukodono Lumajang District, namely p-value 0.001. So that nutritional status can affect the age of menarche, normal nutritional status also affects the normal age of menarche. Therefore, the importance of nutritional intake for the age of menarche, parents should be able to pay attention to their daughter's nutritional intake and nutrition because it can be related to the incidence of menarche experienced by their daughter.